Synthesis, antibacterial activity, synergistic effect, cytotoxicity, docking and molecular dynamics of benzimidazole analogues. (October 2018) - Srivastava, Ritika; Gupta, Sunil K.; Naaz, Farha; Singh, Anuradha; Singh, Vishal K.; Verma, Rajesh; Singh, Nidhi; Singh, Ramendra K.
Graphical abstract: Highlights: Benzimidazole analogues synthesized as antibacterial agents. Molecules were docked with E. coli 16S rRNA A site. Fractional inhibitory concentration showed synergistic effect. MD simulations indicated stable ligand-protein complexes. Cytotoxicity assay proved new molecules less toxic than reference drugs used. Abstract: A series of 2-Cl-benzimidazole derivatives was synthesized and assessed for antibacterial activity. Antibacterial results indicated that compounds 2d, 2e, 3a, 3b, 3c, 4d and 4e showed promising activity against B. cerus, S. aureus and P. aeruginosa (MIC: 6.2 μg/mL) and excellent efficacy against E. coli (MIC: 3.1 μg/mL). Furthermore, compounds 3d and 3e displayed better activity (MIC: 3.1 μg/mL) than the reference drugs chloramphenicol and cycloheximide against gram positive and gram negative bacterial strains. The compounds 3d –e also showed better activity than the reference drug paromomycin against B. cerus and P. aeruginosa and showed similar inhibition pattern against S. aureus and E. coli. (MIC: 3.1 μg/mL). Studies on fractional inhibitory concentration (FIC) determination of compounds 1a –e, 2a –c, 4a –c and the reference antibiotic via combination approach revealed a synergistic effect as the MIC values were lowered up to 1 /8 th to 1 /33 rd of the original MIC. In-vitro cytotoxicity study indicated that 2-Cl-benzimidazole derivatives showed less toxicity than the reference used against PBM, CEM and Vero cell lines. Docking studies and MD simulations of compounds on bacterial protein (eubacterial ribosomal decoding A site, PDB: 1j7t) have been conducted to find the possible mode of action of the molecules. In silico ADMET evaluations of compounds 3d and 3e showed promising results comparable to the reference drugs used in this study.